People without Shoes: Jacques Roumain, Langston Hughes and Their Transnational Ti Nèg Aesthetic. (2nd October 2017) - Willson, Nicole Louise
ABSTRACT: Langston Hughes (1901-1967) was one of the principal trailblazers of the Harlem Renaissance,  paving the course for an artistic and social revolution propelled by racial uplift. This black aesthetic found expression through multiple channels across the Atlantic. In 1931, Hughes travelled to Haiti, where he met the Haitian writer and politician, Jacques Roumain (1907-1944). This encounter sparked an artistic alliance fortified by a shared abhorrence of racial and class inequalities and a mutual interest in the Haitian agrarian poor. Both Hughes and Roumain acknowledged that economic power in Haiti was concentrated in the hands of a privileged elite. Haiti's peasant classes, 'the people without shoes', were nevertheless seen as the true legatees of Haiti's revolutionary culture. In their writings, Hughes and Roumain advanced a shared vision for a transnational peasant aesthetic that celebrated the shoeless revolutionary existence of the Haitian peasantry. This resonated with a nascent black (inter)nationalism that centred around cultural resistance. Read through Elizabeth McAlister's concept of the Haitian  ti nèg, or 'small man', this article interrogates the shared radical vision of Langston Hughes and Jacques Roumain, looking closely at Roumain's novel  Masters of the Dew, translated into English by Hughes after Roumain's death in 1947.